Effect of Mg2+/F− co-doping on electrochemical performance of LiNi0.5Mn1.5O4 for 5 V lithium-ion batteries. (10th November 2019) - Wei, Aijia; Li, Wen; Chang, Qian; Bai, Xue; He, Rui; Zhang, Lihui; Liu, Zhenfa; Wang, Yanji
Abstract: Mg 2+ /F − co-doped LiNi0.5 Mn1.5 O4 cathode material was synthesized by a facile one-step solid-state process. The effect of Mg 2+ /F − co-doping on grain morphology, phase structure, and electrochemical properties was studied by a series of characterizations. Scanning-electron-microscopy images show that Mg 2+ /F − co-doped LiNi0.5 Mn1.5 O4 (denoted LNMO-MF) particles grow larger than pure LiNi0.5 Mn1.5 O4 particles. X-ray diffraction, Raman spectra, Fourier transformation infrared spectroscopy, X-ray photoelectron spectroscopy, and cyclic-voltammetry tests indicate that all samples mainly display a Fd -3m space group and more Mn 3+ ions in the LNMO-MF sample after Mg 2+ /F − co-doping, which is conducive to increasing the cationic disorder degree and enhancing the electronic conductivity of electrode material. Results show that the LNMO-MF cathode material delivers an excellent rate performance with discharge capacities of 142, 144, 140 136, 132, 124, 115, and 100 mAh g −1 at 0.2, 0.5, 1, 2, 3, 5, 7, and 10C (1C = 140 mAh g −1 ), respectively. Remarkably, LNMO-MF also shows cycling stability with a capacity retention of 86.2% at 5C after 400 cycles, which is much higher than that of pure LiNi0.5 Mn1.5 O4 (67.7%). The improvement of LNMO-MF's electrochemical properties could be ascribed to the Mg 2+ /F − co-doping, delivering a more stable structure, better crystallinity, the highest Li + diffusion coefficient, and the lowest charge-transfer resistance.